Effect of exogenous microorganisms on the fermentation quality, nitrate degradation and bacterial community of sorghum-sudangrass silage - Zhao, Meirong; Zhang, Hongyu; Pan, Gang; Yin, Hang; Sun, Juanjuan; Yu, Zhu; Bai, Chunsheng; Xue, Yanlin (Frontiers in Microbiology, 2022)
This study aims to investigate the effects of adding Lactobacillus buchneri (LB), Lactobacillus brevis (LBR) and Bacillus subtilis (BS) on the fermentation quality, nitrate degradation and bacterial community of Sorghum-Sudangrass silage. Sorghum-Sudangrass was harvested at the heading stage and sampled in triplicate after 1, 3, 7, 15 and 40 days of ensiling. The results showed that the addition of LB significantly increased the pH and AA content (P < 0.05), but it was still high-quality silage. The addition of LBR and BS improved the quality of Sorghum-Sudangrass silage, whereas the BS group also significantly increased the CP content (P < 0.05). All silages with additives reduced the nitrate content in sorghum-sudangrass silage. The LB group increased the release of N2O at 3-7 days of ensiling (P < 0.05), and LBR and BS increased the release of N2O during the ensiling process (P < 0.05). The bacteria attached to sorghum-sudangrass were mainly Pantoea. On the first day of ensiling, all silages were dominated by Weisslla, all silages were dominated by Lactobacillus over 3 days of ensiling. The addition of LB illustrated the significance of Weissella and Leuconostocaceae on bacterial abundance, the addition of LBR illustrated the significance of Serratia, Pseudomonas, and Acinetobacter on bacterial abundance and the addition of BS illustrated the significance of Lactococcus, Klebsiella and Aquabacterium on bacterial abundance. Acinetobacter, Serratia, Aquabacterium, and unclasslfied_f_enterobacteriaceae showed a significant negative correlation with nitrate degradation during sorghum-sudangrass ensiling (P < 0.05). Compared with the CK, the BS and LBR groups increased the metabolic abundance of denitrification, dissimilatory nitrate reduction, and assimilatory nitrate reduction (P < 0.05). Overall, the additive does not adversely affect the fermentation quality of Sorghum-Sudangrass silage and promotes the degradation of nitrate by changing the bacterial community.